The effect of specific training of short duration on proximal and distal adjustments at the onset of reaching, in preterm and low birth weight infants: A randomized clinical trial - Guimarães , Elaine Leonezi; Tudella, Eloisa (Seven Editora, 2023)
This study aimed to verify the effect of specific training of short duration on the proximal (uni-and bimanual) and distal (aperture, orientation and the contact surface of the hand) adjustments of reaching, in the period of emergence in preterm infants and with low birth weight. The study included 18 infants of both sexes, born between 29-33 weeks gestational age, weighing less than 2500 grams, and who required peri- and postnatal hospital care. The infants were divided into two groups: experimental and control. The experimental group received a single specific training session (serial varied practice condition) for five minutes, and the control group received no training. Both groups were assessed twice on the same day (pre- and post-training). There was significant difference in the frequency of reaching of the experimental group after training (Z=-2.501, p=0.012) and when compared to the control group (U=17, p=0.037). Significant difference was observed in proximal adjustments where the infants in the experimental group showed more unimanual (Z=-2.252, p=0.024) and bimanual (Z=-2.232, p=0.026) reaching post-training, and between groups differences were observed for bimanual reaching (U=15, p=0.013) in the experimental group after training. In distal adjustments a significant difference was observed in the aperture of the hand (open, U=18, p=0.029), and the orientation of the palm (oblique, U=17.5, p=0.041) between groups. The results indicate that training of short duration enhanced reaching, increasing frequency, and proximal and distal adjustments consistent with age. DOI:https://doi.org/10.56238/alookdevelopv1-188